Nepal : Defending Against Money Laundering: Into and Out of the Grey - Procopio, Joe.; Khetarpaul, Amit. (Washington, D.C. : International Monetary Fund, 2018)
A story about Nepal's journey to address money laundering--how it navigated the various obstacles it faced over the years to meet international standards on anti-money laundering and combating the financing of terrorism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet